REGULASI PENDIDIKAN KARAKTER BAGI MAHASISWA DI FAKULTAS HUKUM UNIVERSITAS SURYAKANCANA DALAM RANGKA MENINGKATKAN SOFTSKILL DAN LITERASI KEUANGAN - Tanti Kirana Utami; M. Rendi Aridhayandi (Universitas Suryakancana, 2020)
Student morality and character are in the spotlight when experiencing erosion, so character education that has been taught is not only a learning theory but a practice of student life when studying on campus. Through the development of an innovative curriculum that aims to improve skills through training to improve student soft skills and finance is very important because in these training activities students can further improve life skills (soft skills) and financial management skills that can support student readiness to enter the job market. and the business world, which can then help improve their economic welfare in the future with a training program to improve soft skills and finance or Financial Life Skills (FLS). The Faculty of Law, Suryakancana University refers to various applicable laws and regulations, which are set forth in the form of a Dean's decree regarding graduate competence.Keywords : Financial Life Skill (FLS), Character, Morality, Training Soft Skills Improvement.